ANALYSIS OF THE MEANING OF THE TARUNG SARONG FILM - Hanum, Alya Maulidia; Simanjuntak, Marudud Bernadtua (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Literary works, especially literature and culture can also be seen from films as art. "Tarung Sarong" is an Indonesian action film featuring elements of religion, self-defense and the culture of the archipelago. This film is very interesting as well as thick with culture, religion, and the invitation to the existence of Mark for an environment. Through this film, we are introduced to the culture of Sigajang lalang lipa which is the culture of the Bugis people in maintaining their dignity or honor when there are problems/problems. In this study, this study aims to find out how the meaning contained in the tarung film sarong. This study is expected to have a positive impact in understanding the storyline in the film. The research method used in this study is a qualitative method. The results of this study indicate that the film sarong is a film that has many positive meanings such as religion, culture, and martial arts.